Environmental Enrichment and Prosocial Behavior in Wistar Rats: an Exploratory Study (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
This research aimed to experimentally explore how rats reared in environmental enrichment (EE) and in isolation (ISO) behave in the prosocial behavior liberation task. The subjects were reared in two conditions: EE and ISO, and then submitted to the task. The results suggests that EE subjects spent more time near the restrainer, displayed faster door-opening behavior but interacted less with the released conspecific task compared with the ISO subjects. Our preliminary findings suggest that the rearing conditions may affect prosocial behavior, and that EE may increase the probability of displaying prosocial behavior. We discussed the need of more studies about the effect of rearing conditions and how it may impact motivations associated with the prosocial behavior and its consequences.
Keywords: Rats; Environmental Enrichment; Prosocial Behavior; Helping Behavior